What is the possible origin of the 195Pt NMR shielding in the solid state? X-ray diffraction, solid-state NMR studies of deceptively simple C2[PtX6] salts (C = various cations, X = Cl- and Br-) - Odendal, James Arthur (Stellenbosch : Stellenbosch University, 2015)
Thesis (DSc)--Stellenbosch University, 2015.